Windborne migration amplifies insect-mediated pollination services - Huiru Jia (eLife, 2022)
Worldwide, hoverflies (Syrphidae: Diptera) provide crucial ecosystem services such as pollination and biological pest control. Although many hoverfly species exhibit migratory behavior, the spatiotemporal facets of these movement dynamics, and their ecosystem services implications are poorly understood. In this study, we use long-term (16-year) trapping records, trajectory analysis, and intrinsic (i.e., isotope, genetic, pollen) markers to describe migration patterns of the hoverfly Episyrphus balteatus in northern China. Our work reveals how E. balteatus migrate northward during spring–summer and exhibits return (long-range) migration during autumn. The extensive genetic mixing and high genetic diversity of E. balteatus populations underscore its adaptive capacity to environmental disturbances, for example, climate change. Pollen markers and molecular gut analysis further illuminate how E. balteatus visits min. 1012 flowering plant species (39 orders) over space and time. By thus delineating E. balteatus transregional movements and pollination networks, we advance our understanding of its migration ecology and facilitate the design of targeted strategies to conserve and enhance its ecosystem services.